2007
DOI: 10.1007/s10554-007-9248-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with aortic enlargement and increased stiffness: an echocardiographic study

Abstract: Aortic stiffness is higher in young obese patients and similar to older subjects without obesity. Both SD and DD are increasing with age, but subjects within similar age group have larger SD and DD suggesting early vascular remodelling in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
4
18
3
Order By: Relevance
“…Obesity is associated with an increase in aortic pulse wave velocity (PWV) and/or intrinsic stiffness (assessed by the stress-strain relationship) in human subcutaneous small resistance arteries 6,[11][12][13] , as well as in aorta of high-fat/high-sucrose SD 7 or in genetic models of obesity, i.e. ob/ob mice 14 and insulinresistant Zucker fa/fa rats 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is associated with an increase in aortic pulse wave velocity (PWV) and/or intrinsic stiffness (assessed by the stress-strain relationship) in human subcutaneous small resistance arteries 6,[11][12][13] , as well as in aorta of high-fat/high-sucrose SD 7 or in genetic models of obesity, i.e. ob/ob mice 14 and insulinresistant Zucker fa/fa rats 8 .…”
Section: Introductionmentioning
confidence: 99%
“…According to this, several studies have shown a link between arterial stiffness and abnormal increase in the collagen/elastin ratio in hypertension 18,[24][25][26] . However, very few studies 11,12 have been performed in the context of obesity, and the role of obesity per se in the development of mechanical abnormalities remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In general cardiology practice, stiffness is considered a pivotal marker of aortic elastic properties that independently predicts cardiovascular disease morbidity and mortality [5]; thus the determination of aortic stiffness among atopic patients (as was done for psoriatic persons) seemed to be a logical approach to elucidate the cardiovascular interference of AD. We measured aortic stiffness parameters (aortic stiffness index, strain and distensibility) in young adult probands with AD [mean age 30.5 ± 10.8 years, 11 women and eight men, body mass index (BMI) 28.3 ± 3.5 kg/m 2 ] and without AD (mean age 29.3 ± 2.9 years, 11 women and eight men, BMI 29.5 ± 4.8 kg/m 2 ).…”
mentioning
confidence: 99%
“…Chronic inflammation (e.g., psoriasis, inflammatory bowel disease [9], rheumatoid arthritis [10], obesity [5]) has been shown to be associated with altered aortic stiffness parameters, and AD may influence aortic elasticity with this property, too.…”
mentioning
confidence: 99%
“…We have recently shown that obesity is associated with aortic enlargement and increased stiffness regardless the age of patients (44).…”
Section: Aortic Distensibility Alterations In Lipoedemamentioning
confidence: 97%